2017
DOI: 10.1016/j.athoracsur.2017.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Aorta Stenting After Off-Pump Aortic Wrapping in Stanford A Retrograde Aortic Dissection

Abstract: We report 4 cases of off-pump ascending aorta wrapping combined with ascending aorta stenting in retrograde Stanford A acute aortic dissection (SAAD). Since 2008, 18 patients have undergone wrapping of the ascending aorta at our institution. Four patients had a persistent circulating false lumen in the ascending aorta after wrapping, with a threat to the aortic root. We chose an endovascular approach with ascending aorta stenting. Follow-up computed tomography showed a reapplication of the intimal flap in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Postoperative computed tomography scan imaging showed complete regression of the false lumen in the ascending aorta after surgery, except in 4 patients who underwent successful complementary endovascular stenting due to persistent circulating false lumen. 3 In case of secondary aneurysmal evolution of the non-wrapped aortic arch, we recently reported that 88% of our cohort could be candidates for additional endovascular arch repair. 4
Figure 1 Schematic diagram of an aortic wrapping performed around the dissected ascending aorta using a Teflon (Chemours, Wilmington, DE) plaque.
…”
mentioning
confidence: 75%
“…Postoperative computed tomography scan imaging showed complete regression of the false lumen in the ascending aorta after surgery, except in 4 patients who underwent successful complementary endovascular stenting due to persistent circulating false lumen. 3 In case of secondary aneurysmal evolution of the non-wrapped aortic arch, we recently reported that 88% of our cohort could be candidates for additional endovascular arch repair. 4
Figure 1 Schematic diagram of an aortic wrapping performed around the dissected ascending aorta using a Teflon (Chemours, Wilmington, DE) plaque.
…”
mentioning
confidence: 75%